THEORY AND TECHNIQUES OF LEARNING GERMAN. - Sultanova Muxabbat Shamsievna (Scholar Express Journal, 2022)
The relevance of the study is an increased interest in the rules governing the compatibility of sound elements of a language and in their functioning is characteristic of all modern linguistics. Therefore, new studies of consonant combinations in different languages become necessary. The choice of the research of this study was determined by the following reasons until now, the vast majority of researchers have used the material of monosyllabic words in the study of phonetic features of the language polysyllabic words, according to our observations, characterize the language and its vocabulary
Keywords: German Language; issues; learning; pedagogy